2015
DOI: 10.1186/s12879-015-1266-4
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes of group B streptococci in western Sweden and comparison with serotypes in two previous studies starting from 1988

Abstract: BackgroundGroup B Streptococci (GBS) are the most common neonatal pathogens and infect immunocompromised and elderly individuals. The species has 10 different serotypes. Serotypes have been studied in the south-west area of Sweden in 1988–1997 and 1998–2001. The aim of this study was to study serotypes in the same area from 2004 to 2009.MethodsInvasive GBS isolates were collected prospectively from 2004 to 2009 in two counties in western Sweden with a population of 1.8 million, and were serotyped by latex aggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
13
0
2
Order By: Relevance
“…As mentioned above, a study in southern Ghana observed CPS IX as having the second highest prevalence, behind CPS VII (47). A Swedish study assessed changes in serotype distribution over time for invasive disease (neonatal and adult populations) and suggested that circulating serotypes remained stable from 1990 onwards; however, the study noted an increase in CPS VII to IX (55). Additionally, a case study in Japan described an incidence of ultra-late-onset sepsis caused by CPS IX, and this demonstrates its capacity to play a role in disease (56).…”
Section: Serotypingmentioning
confidence: 97%
“…As mentioned above, a study in southern Ghana observed CPS IX as having the second highest prevalence, behind CPS VII (47). A Swedish study assessed changes in serotype distribution over time for invasive disease (neonatal and adult populations) and suggested that circulating serotypes remained stable from 1990 onwards; however, the study noted an increase in CPS VII to IX (55). Additionally, a case study in Japan described an incidence of ultra-late-onset sepsis caused by CPS IX, and this demonstrates its capacity to play a role in disease (56).…”
Section: Serotypingmentioning
confidence: 97%
“…Studies in Malawi [19], Finland [20], Sweden [21], England [22], United States [23], Zimbabwe [18], Gambia [24], Egypt [25] and in Brazil [26] have shown variations in serotype distribution around the world. This study therefore sought to determine the prevalence of GBS and capsular type distribution of isolates colonising pregnant women in Namibia and South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results are consistent with the available literature data [ 17 , 20 , 34 , 38 ]. The occurrence of individual serotypes (Ia, Ib, and II–IX) is different, depending on the geographical region of the world and ethnicity assessed; it also changes for a given region over the time [ 39 , 40 , 41 , 42 ]. Among 353 strains isolated from pregnant women from the Małopolska province in Poland, the serotypes III (35%) dominated among the tested strains, followed by Ia (20%), V (17%), II (15%), Ib (8%), and IV (5%) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%